Fe/ppm Cu nanoparticles as a recyclable catalyst for click reactions in water at room temperature. Issue 11 (10th May 2017) - Adenot, Aurélien; Landstrom, Evan B.; Gallou, Fabrice; Lipshutz, Bruce H.
Abstract : Nanomicelles housing a terminal alkyne and azide are delivered to ppm Cu-containing nanoparticles that catalyse click reactions in water at rt. Abstract : New iron-based nanoparticles doped with ppm levels of CuOAc are capable of catalyzing cycloadditions between alkynes and azides to afford triazole-containing products. These reactions take place in water at ambient temperatures, enabled by the presence of nanomicelles that function as a delivery mechanism. The NPs can be easily recycled within the same reaction vessel. Low levels of residual copper are found in the product.